Study on the adhesive property of sludge-modified magnesium phosphate cement reinforcement coating for steel bars - Shusen, Zhang; Jiapeng, Yang; Yiyang, Li; Zhenyu, Wang; Shunjie, Zhong; Liling, Zhuang; Tao, Wang (Frontiers in Materials, 2024)
Different sludge-modified magnesium phosphate cement mixtures were applied on the surfaces of plain round steel bars and ribbed steel bars to prepare steel-reinforced concrete specimens. Pull-out tests were conducted using a universal testing machine after 28 days of specimen curing. Through analyzing the failure modes, bond strength, and slip values of different groups, the bond performance of the sludge-modified magnesium phosphate cement reinforcement coating for steel bars and concrete was characterized. Microscopic analysis was performed using a scanning electron microscope. The results indicated that the primary failure mode of the steel-reinforced concrete specimens was steel bar pull-out, with some groups showing concrete splitting failure. Application of the coating on plain round steel bars resulted in an increase in bond strength, while its application on ribbed steel bars led to a decrease in bond strength. Coating application reduced slip values to some extent, although the decrease was minimal.